2020
DOI: 10.1038/s41586-020-2493-4
|View full text |Cite|
|
Sign up to set email alerts
|

Expanded encyclopaedias of DNA elements in the human and mouse genomes

Abstract: Cell lines were not tested for mycoplasma contamination. Commonly misidentified lines (See ICLAC register) No commonly misidentified cell lines were used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

19
1,060
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 1,505 publications
(1,166 citation statements)
references
References 71 publications
19
1,060
0
Order By: Relevance
“…Fortunately, the recent development of ChIP-seq techniques for locating histone marks(Barski et al, 2007) and TF bindings in genomes in specific cell/tissue types(Johnson, Mortazavi, Myers, & Wold, 2007) has led to the generation of enormous amounts of data by large consortia such as ENCODE(Moore et al, 2020), Roadmap Epigenomics(Kundaje et al, 2015) and Genotype-Tissue Expression (GTEx)(Consortium, 2015), as well as individual labs worldwide(Mei et al, 2017). These increasing amounts of ChIP-seq data for relevant histone marks and various TFs in a wide spectrum of cell/tissue types provide an unprecedented opportunity to predict a map of CRMs and constituent TFBSs in the human genome.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Fortunately, the recent development of ChIP-seq techniques for locating histone marks(Barski et al, 2007) and TF bindings in genomes in specific cell/tissue types(Johnson, Mortazavi, Myers, & Wold, 2007) has led to the generation of enormous amounts of data by large consortia such as ENCODE(Moore et al, 2020), Roadmap Epigenomics(Kundaje et al, 2015) and Genotype-Tissue Expression (GTEx)(Consortium, 2015), as well as individual labs worldwide(Mei et al, 2017). These increasing amounts of ChIP-seq data for relevant histone marks and various TFs in a wide spectrum of cell/tissue types provide an unprecedented opportunity to predict a map of CRMs and constituent TFBSs in the human genome.…”
Section: Introductionmentioning
confidence: 99%
“…Many enhancer databases have also been created either by combining results of multiple such methods(Ashoor, Kleftogiannis, Radovanovic, & Bajic, 2015; Fishilevich et al, 2017; Zerbino, Wilder, Johnson, Juettemann, & Flicek, 2015), or by identifying overlapping regions of CA and histone mark tracks in the same cell/tissue types(Chen et al, 2020; Cheneby, Gheorghe, Artufel, Mathelier, & Ballester, 2018; Gao & Qian, 2020; Kang et al, 2019; G. Zhang et al, 2018). In particular, most recently, the ENCODE phase 3 consortium(Moore et al, 2020) identified 926,535 candidate cis -regulatory elements (cCREs) based on overlaps between millions of DNase I hypersensitivity sites (DHSs)(Thurman et al, 2012) and transposase accessible sites (TASs)(Buenrostro, Giresi, Zaba, Chang, & Greenleaf, 2013), active promoter histone mark H3K4me3(Aday, Zhu, Lakshmanan, Wang, & Lawson, 2011) peaks, active enhancer mark H3K27ac(Creyghton et al, 2010) peaks, and insulator mark CTCT(Kim et al, 2007) peaks in a large number of cell/tissue types. Although CRMs predicted by these methods are often cell/tissue type-specific, their applications are limited to cell/tissue types for which the required datasets are available(Ernst & Kellis, 2012; Hoffman et al, 2013; Moore et al, 2020; Won, Chepelev, Ren, & Wang, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations